3D numerical simulations of passive mixing in a microchannel with nozzle-diffuser-like obstacles. (October 2016) - Ritter, P.; Osorio-Nesme, A.; Delgado, A.
Highlights: Mixing by chaotic advection in a microchannel with asymmetric obstacles is studied. The asymmetric obstacle arrangement promotes transverse flow. At high Peclet number, the chaotic advection is observed with helical and intertwined flow patterns. The proposed microchannel enhanced mixing efficiently for Pe > 100. Abstract: A novel passive chaotic advection micromixer with periodic nozzle-diffuser-like (NDL) obstacles is proposed. Lattice Boltzmann simulations of two incoming flows were performed for Reynolds numbers in the range 1 ⩽ Re ⩽ 100 and two Schmidt numbers Sc = 1 and 50. The numerical study focuses on the evaluation of the mixing efficiency of the new design and the analysis of mass transfer as a function of the Péclet number. The flow was identified as spatially periodic. The results are compared with those for a plain rectangular channel. The asymmetric design and placement of the obstacles lead to splitting and recombination of the flows, promoting transverse flow. Two principal characteristics of chaotic advection were observed at high Pe: helical, intertwined streamlines and hyperbolic points in transverse planes. The mixing efficiency was found to increase with channel length, whereas for the proposed channel the mixing efficiency was observed higher than that for the rectangular channel for Pe > 100 .